Sequencing CONWIP flow-shops: Analysis and heuristics - Jose M. Framiúnan; Rafael Ruiz-Usano; Rainer Leisten (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 1998)
In this paper, we address the backlog sequencing problem in a flow-shop controlled by a CONproduction control system with the objective to minimise the make span We characterise the problem and analyse its similarities and differences with the permutation flow-shop problem A comparison of same well-known flow-shop heuristics is carried out and a simple and fast dispatching rule is proposed. Regarding the more simple and faster heuristics, the proposed dispatching rule outperforms those commonly used for the permutation flow-shop problem.
Keywords: 330; Scheduling; Sequencing; Flow-Shop; Constant Work in Process (CONWIP); Heuristics; Dispatching Rules